Recurrence Relations for Single and Product Moments of Dual Generalized Order Statistics from a General Class of Distributions - Jagdish Saran; Narinder Pushkarna; Rashmi Tiwari (Journal of Statistical Theory and Applications (JSTA), 2015)
In this paper we derive some general recurrence relations between single and product moments of dual gener- alized order statistics from a general class of distributions, thus generalizing and unifying the earlier results in this direction due to several authors.